Between Theology and History: Re-evaluating the Solar Eclipse Narrative in the Karbala Tragedy through Islamic Historiography and Astronomy - Muhammad Himmatur Riza; Ahmad Adib Rofiuddin; Moelki Fahmi Ardliansyah; Restu Trisna Wardani; Ahmad Roihan Firdiansyah (Universitas Muhammadiyah Bandung, 2026)
This study critically examines the widely circulated claim that a solar eclipse occurred on the day of Ḥusayn ibn ʿAli’s martyrdom during the Karbala tragedy (10 Muḥarram 61 AH / 10 October 680 CE). While the narrative appears in classical sources such as Tārīkh al-Khulafā’ by al-Suyuthi, it has rarely been subjected to rigorous interdisciplinary verification. This research addresses that gap by integrating historical-textual criticism with astronomical data analysis. Using a qualitative library-based approach, the study evaluates the reliability of the narrative through isnād and matn criticism, while cross-referencing it with NASA eclipse records and Stellarium simulations. The findings demonstrate that no solar eclipse occurred or was observable in the region on the stated date, thereby contradicting the historical claim. This suggests that the eclipse narrative functions primarily as a symbolic and theological construct rather than an empirical event. The study contributes to Islamic historiography by emphasizing the importance of methodological integration between traditional scholarship and modern scientific tools, offering a clearer distinction between symbolic religious narratives and historically verifiable facts.